Termos de consentimento livre e esclarecido: o gênero e sua estruturação - Quadros, Carmen Regina Teixeira de (Universidade do Vale do Rio do Sinos, 2006)
The goal of this work is to analyze Informed Consent texts (TCLE), used at the referring of research projects to Ethics Committees’ evaluations, concerning to the Resolution 196/96. This kind of study is relevant because of the research community’s necessity to elaborate those texts in a clear and cohesive way, so that people are able to understand them. To the study, 30 texts of three different institutions were analyzed, all of them approved by the institutions’ Ethics Committees. This material was analyzed in three different moments, and it is based on Jean Paul Bronckart’s theory (1999), which understands the text organization as a leaf with three layers. The first moment is about the general structure of the text, which has the following parameters: the TCLE thematic, predominant kind of discourse, presented textual sequences, joint between these sequences; the second is about the analyses of the texts mechanisms, where the parameters thematic coherence, nominal and verbal cohesion, as well as logical-ti
Keywords: consentimento livre; folhado textual; lingüística textual; gênero textual; consent term; text leaf; gender; Letras e Artes; Lingüística